Evolution of clinical characteristics of patients with paroxysmal nocturnal hemoglobinuria treated with eculizumab in turkey: a multicenter retrospective analysis - (:unkn) unknown (E-CENTURY PUBLISHING CORP, 2021)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare X-linked genetic disorder. On the contrary to its name, it is a multisystemic disease and various symptoms other than hemoglobinuria could be occurred. It could be life threatening especially because of thromboembolic events. In the last decade, a terminal complement inhibition with eculizumab approved with promising results for PNH patients. We conducted this study to evaluate the long term experience of eculizumab therapy from Turkey for the first time. Our cohort included 138 patients with PNH treated with eculizumab between January 2008 and December 2018 at 28 centers in Turkey. Laboratory and clinical findings at the time of diagnosis and after eculizumab therapy were recorded retrospectively. The median age was 39 (range 18-84) years and median granulocyte PNH clone size was 74% (range 3.06-99.84%) at the time of diagnosis. PNH with bone marrow failure syndrome was detected in 49 patients and the rest of 89 patients had classical PNH. Overall 45 patients (32.6%) had a history of any prior thrombotic event before eculizumab therapy and only 2 thrombotic events were reported during the study period. Most common symptoms are fatigue (75.3%), hemoglobinuria (18.1%), abdominal pain (15.2%) and dysphagia (7.9%). Although PNH is commonly related with coombs negativity, we detected coombs positivity in 2.17% of patients. Seven months after the therapy, increased hemoglobin level was seen and remarkably improvement of lactate dehydrogenase level during the treatment was occurred. In addition to previous studies, our real life data support that eculizumab is well tolerated with no serious adverse events and improves the PNH related findings.
Keywords: PNH; eculizumab; LDH; hemolysis; coombs test; COMPLEMENT INHIBITOR ECULIZUMAB; DISEASE BURDEN; MANAGEMENT; THROMBOSIS; DIAGNOSIS; HEMOLYSIS